Linezolid and serotonin syndrome - Haytham A. Wali (Journal of International Medical Research)
Linezolid, a synthetic oxazolidinone antibiotic, is used to treat gram-positive bacterial infections, including methicillin-resistant Staphylococcus aureus . Despite its efficacy, linezolid can cause serotonin syndrome, a potentially fatal condition associated with excessive serotonin activity in the brain. This narrative review examined the pharmacological mechanisms of this interaction, particularly linezolid’s mild monoamine oxidase-inhibitory activity, which can trigger serotonin syndrome in combination with serotonergic drugs. Serotonin syndrome causes cognitive, autonomic, and somatic symptoms ranging from mild (tremors, diarrhea) to severe (hyperthermia, seizures, multiorgan failure). The Hunter Serotonin Toxicity Criteria have superior sensitivity and specificity over the Sternbach Criteria for diagnosis. Clinical evidence indicates that although the incidence of linezolid-induced serotonin syndrome is low, the risk justifies careful monitoring and risk assessment. This review emphasizes enhanced pharmacovigilance and standardized reporting criteria to better capture and analyze data on linezolid-induced serotonin syndrome. Assessments of the pharmacological mechanisms, large-scale clinical trials, and cohort studies are essential to elucidate risk factors and outcomes. Developing comprehensive clinical guidelines and education programs for healthcare providers is crucial to improve linezolid’s safety profile. Exploring pharmacogenomic approaches and alternative therapies with lower serotonin syndrome risks is recommended to enhance patient outcomes while maintaining linezolid’s efficacy in treating severe bacterial infections.